A vicious cycle of symbolic tokenism: The gendered effects of external board memberships on chief executive officer compensation. Issue 4 (28th January 2021) - Malhotra, Shavin; Shen, Winny; Zhu, PengCheng
Abstract: Integrating theoretical perspectives on tokenism and perceived preferential selection, we explore whether the relationship between chief executive officers' (CEOs') external board memberships and CEO compensation is gendered. Based on recent pressures to diversify corporate boards, we theorize that female CEOs' memberships on external boards will result in less monetary compensation relative to male CEOs due to concerns of organizational decision‐makers that female CEOs generally inhabit token or "symbolic" positions of limited value. Additionally, we present competing hypotheses (i.e., mitigation vs. exacerbation) regarding how this devaluation will be affected by female representation on the board of directors and compensation committee, respectively. Using a panel sample of 12, 464 firm‐year observations comprising of 1, 805 unique firms and 2, 782 unique CEOs, the relationship between CEO external board memberships and compensation is indeed weaker for female compared to male CEOs. Furthermore, this devaluation primarily occurred in organizations where there was stronger (vs. weaker) female representation on the board of directors or compensation committee. However, supplemental analyses revealed that this differential devaluation was mitigated when female executives on the board held greater power (i.e., chaired important committees), highlighting the importance of moving beyond mere representation to ensuring influence on boards for female directors.